PENGARUH EXPERIENTAL MARKETING DAN EVENT MARKETING TERHADAP LOYALITAS KONSUMEN DI UMA GRILL CAFE - Putri Maulidian; Sri Ernawati; Kartin Aprianti Put (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
This research aims to determine Experiential Marketing and Event Marketing on consumer loyalty at Uma Grill Cafe. The type of research used is associative. The population in this study were all consumers who had visited Uma Grill Cafe. The sample in this study was 50 people using a purposive sampling technique. The research instrument uses a questionnaire with Likert scale measurements. The type of data used in this research is quantitative data with the research data source being primary data. Data collection techniques are observation, questionnaires/questionnaires and literature study. Data analysis uses validity test, reliability test, classical assumption test, multiple linear regression test, determination test, correlation test, t test and F test. The results of the study show that Experiential marketing has no effect on consumer loyalty at Uma Grill Cafe, Event marketing has an effect on consumer loyalty to uma grill cafe and together Experiential marketing and event marketing influence consumer loyalty to uma grill cafe